Too uncool for school - Patterson, James, 1947-; Chatterton, Martin (Patterson, James, 1947- Middle school novels, 2025)
Rafe Khatchadorian finally gets a taste of popularity when he joins a rock band and lands a job at a trendy coffee shop, but his plans hit a snag when the band is terrible and led by the school bully, leaving Rafe struggling to save both his coolness and his chance at the Best Band Competition.